Improving Narrative Writing Ability Using Model Problem Based Learning Based on Mind Mapping - Eli Nurliza (Jurnal Serambi Ilmu, 2021)
The purpose of this study is to find out how to increase students' narrative skills by using a mind mapping-based problem-based learning model, to find out how effective the use of mind mapping-based problem-based learning models in writing scientific narratives . Sources of the data were students of class V Elementary School 1 Lambheu totaling 52 students consisting of two classes, namely class A totaling 26 students and class B totaling 26 students. One class as an experimental class by using the problem base learning method based on mind mapping and the other class as a control class is a class whose learning is not given treatment. The data processing tool is using statistics with the help of SPSS for Windows Version of the Standard 16.0. The results showed that the ability of students to write narratives who received learning using the problem base learning method based on mind mapping was better than students who received conventional narrative learning as a whole.